Effects of Density Variation on the Physical and Mechanical Properties of Empty Fruit Bunch Cement Board (EFBCB) - Ridzuan, Mohammad Nasrullah; Abu Bakar, Hasniza; Samsudin, Emedya Murniwaty; Nik Soh, Nik Mohd Zaini; Ismail, Lokman Hakim (Pertanika, 2023)
A cement board is a composite material mostly comprised natural fibre and cement. Cement board is mainly used in roofing, raised floors, dropped ceilings, prefabricated structures,office containers, and other building components. Fibres in cement composites from discarded palm oil fruit bunches have been used to increase the quality of construction materials. Therefore, the impact density of the natural fibre cement board is essential to enhance the physical and mechanical properties. However, research on untreated fibre at various densities has not been compressively discussed in previous studies. Therefore, this research used empty fruit bunch (EFB) fibre in manufacturing empty fruit bunch cement boards (EFBCB) with a cement-to-fibre ratio of 3:1 and thickness of 12 mm. Three target density variations, 1100 kg/m3 , 1200 kg/m3 and 1300 kg/m3 , were applied in this study to obtain their effect on physical and mechanical properties. The results revealed EFBCB sample with a target density of 1300 kg/m3 showed the most promising results. This sample’s average thickness is 12.38 mm after a 28-day curing period. Besides, at 1300 kg/m3 target density, EFBCB achieved the lowest thickness swelling (TS) value at 1.82%, highest internal bonding (IB) at 0.164 N/mm2 , highest modulus of elasticity (MOE) and modulus of rupture (MOR) at 1398 N/mm2 and 3.51 N/mm2 , respectively. Thus, increasing the cement board density and improving the physical and mechanical properties of EFBCB. This study demonstrates that EFB has the capacity to be one of the potential natural fibres for green building materials.